Osteoblast behaviour on zirconia fabricated by additive and subtractive technology - Roser, Christoph; Erber, Ralf; Rammelsberg, Peter; Lux, Christopher J.; Kurt, Aysegul; Rues, Stefan; Schwindling, Franz Sebastian; Herpel, Christopher (Ceramics international, 2023)
Zirconia is an attractive material for the manufacturing of oral implants and patient-individual barriers for guided bone regeneration. This study compared osteoblast behaviour on additive manufactured and milled 3-mol% yttria-stabilized tetragonal polycrystal zirconia (ZrO2). ...